STUDI EVALUASI TENTANG KOMPETENSI PEDAGOGIK GURU PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM PELAKSANAAN PENILAIAN PSIKOMOTOR (STUDI DI SMP NEGERI 3 KEBAKKRAMAT KARANGANYAR) - Fadrusiana, Erna Gesti; ., Rusnaini; Nuryadi, Muh Hendri (PKn Progresif, 2016)
This study aims to ascertain:  1) How the competence of civics teachers as implementation of psychomotor rating. 2) What are the inhibiting factors that experienced by civics teachers as implementation of psychomotor rating towards students at Junior High School 3 Kebakkramat Karanganyar.This method on this research is using a qualitative research approach. The type of research is qualitative descriptive. Data source obtained from informant, place, event and document. Sampling technique which used is purposive sampling. In this research, data collection techniques used to obtain and arrange data by interview, observation and document analysis. In the research results, it can be concluded that: 1) pedagogical competence of Civics teacher in implementing rating has been done, but it is not all explanation in each indicators done by civics teachers. In indicator implements rating, process evaluation, and study result, civics teachers have not done yet the administration of process rating and study result chronically by using various instrument. For the indicator of utilizing research result and evaluation to the interest of learning, civics teachers have done well. Also, the indicator doing reflective action of increasing quality of learning. Civics teachers have done it but civics teachers have not done yet research of class action that obtained by that reflective result to improve learning on civics subject. In addition, As for psychomotor rating showed by unsuitable RPP in the making of implementing in class. Teachers apply the psychomotor rating on RPP but it can?t be done yet in learning. Civics teachers in psychomotor rating using technique of rating for job, portfolio, and observation or self-judging; 2) The inhibiting factors that hampered by Civicsteachers on determining of Psychomotor Rating are: hampered by time, difficult to determine the indicator and evaluation aspects of learning materials, the number of students are big, using cognitivist teaching materials and conventional learning models.